2018
DOI: 10.1002/masy.201600192
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization of Titania/Polyaniline/GO Nanocomposites, and Its Photocatalytic Activity Under UV‐Visible Light

Abstract: In the present study, to prepare the TiO2, TiO2/PAni, and TiO2/PAni/GO nanocomposites wet chemical method and they are used as photocatalyst for the photodegradation of Vitoria Blue B dye. The prepared TiO2, TiO2/PAni, and TiO2/PAni/GO are subjected to XRD analysis, which gives the information about the presence of phase rutile and anatase both phases are present in the samples. The SEM and TEM of the prepared samples are shown in the particles morphology. The prepared samples are found in nanodiamension. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The photodegradation rate and TOC increased with the concentration of gentian violet up to 0.25 mM and then declined, as shown in Figure 9a. Kumar et al reported that the degradation efficiency of VBB over TiO 2 /polyaniline (PAni)/graphene oxide (GO) decreased with an increase in initial dye concentration [67], as shown in Figure 9b. This phenomenon was studied for other dye molecules, including the AR14/TiO 2 [3] and other systems [13,14,68,69].…”
Section: Initial Dye Concentrationmentioning
confidence: 95%
“…The photodegradation rate and TOC increased with the concentration of gentian violet up to 0.25 mM and then declined, as shown in Figure 9a. Kumar et al reported that the degradation efficiency of VBB over TiO 2 /polyaniline (PAni)/graphene oxide (GO) decreased with an increase in initial dye concentration [67], as shown in Figure 9b. This phenomenon was studied for other dye molecules, including the AR14/TiO 2 [3] and other systems [13,14,68,69].…”
Section: Initial Dye Concentrationmentioning
confidence: 95%
“…FC technology has the potential to revolutionize the heavy‐duty vehicle sector by providing a cleaner and more efficient alternative to traditional combustion engines [222] . Heavy‐duty vehicles are a considerable source of air pollution and consequent human deaths [223,224] . The emission of nitrogen oxide from heavy‐duty vehicles poses a serious environmental concern, [225] with the global warming potential of nitrogen oxide is 273 times higher than that of CO 2.…”
Section: Future Outlook Of Fuel Cellsmentioning
confidence: 99%